Art and logic In Hegel's philosophy / edited by Warren E. Steinkras and Kenneth I. Schmitz - "Steinkraus, Warren E. (ed.)" (Sussex, 1980)
Each previous volume in this series has centered upon a single theme in Hegel's philosophy. All have been based upon papers presented at biennial meetings of the Hegel Society of America. The first conference was held at Wofford College and dealt with Hegel and the philosophy of Religion.
Keywords: "Hegel, Georg Wilhelm Friedrich, 1770 - 1831 - Aesthetics"